Varicella Zoster-related Occlusive Retinal Vasculopathy—A Rare Presentation. (3rd March 2016) - Narayanan, Sandhya; Gopalakrishnan, Mahesh; Giridhar, Anantharaman; Anthony, Eliza
Abstract: Purpose : To report a case of occlusive retinal vasculopathy following varicella zoster infection in an immunocompetent adult. Design : Observational case report. Methods : A patient with defective vision following chickenpox was evaluated with fluorescein angiography, spectral domain optical coherence tomography and fundus auto fluorescence. Results : Fundus showed multiple cotton wool spots and a well-demarcated zone of retinal ischemia in the posterior pole with normal optic disc without any evidence of anterior or posterior uveitis. Fluorescein angiography, spectral domain optical coherence tomography and fundus auto fluorescence findings revealed occlusive vasculopathy as the cause of defective vision. Conclusions : We report a hitherto undescribed case of purely occlusive vasculopathy following varicella zoster infection without features of vasculitis or anterior and posterior uveitis in an immunocompetent individual.